Value, money and risk : three essays - Li, Matthew C. (Trinity College (Dublin, Ireland). Department of Economics, 2003)
This thesis comprises of three essays which explore the theories of value, money and risk. The first essay takes a theoretical approach to study the background of and the relationship between value, money and wealth. The second and third essays examine empirically the issue of risk at both domestic and international levels.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin